The Influence of Flashcard for the Early Reading and Writing Ability of First-Grade Elementary School Students - Ai Komalasari; Firmanul Catur Wibowo; Juhana Juhana (Universitas Muhammadiyah Enrekang, 2023)
The research was conducted to: (1) determine the effect of using flashcard on the early reading skills of the first-grade elementary school students in the Pandeglang District; (2) assess the effect of using flashcard on the early writing ability of the first-grade elementary school students in the Pandeglang District; and (3) find out the difference in the impact of with and without using flashcard on the early reading skills of the first-grade elementary school students in the Pandeglang District. The current research employed quantitative approach with experimental methods. Data collection techniques were pre-test and post-test and observations. The population was all elementary schools in the Pandeglang sub-district, and the sample of the study was four elementary schools that were randomly selected, namely SD Negeri Pandeglang 9, SD Negeri Pandeglang 7, SD Negeri Pandeglang 10, and SD Negeri Pandeglang 11 for the 2018/2019 academic year. The data analysis technique was through statistical analysis with prerequisite analysis tests, namely normality and homogeneity tests, then hypothesis testing through paired T-test. The results showed a significant effect of using flashcards on the ability to read and write at the beginning of the first-grade elementary school students in the Pandeglang District. There were differences in the effect of student learning outcomes with and without flashcard on the ability to read and write at the beginning of the first-grade elementary school students in the Pandeglang District, Pandeglang Regency.